Emulating the Struggle of A.K. Gani (1945–1949) in Efforts to Instill the Character of Love for the Homeland - Rieca Nona Mutia; Suranto Suranto (MASI Mandiri Edukasi, 2026)
A.K. Gani was one of the fighters during the physical revolution (1945-1949), A.K. Gani was awarded the title of national hero in 2007 for fighting for the Palembang region. Although A.K. Gani did not come from and was born from Palembang, but he was still persistent and brave in fighting to defend Indonesia's independence based on his spirit of love for his homeland. The spirit of love for one's country is one of the values of character education that must be instilled in students. The aim of writing this article is to instill a spirit of love for the country that AK can emulate. Gani as a fighter figure for the Physical Revolution (1945-1949) in Palembang, and provides information and insight for students regarding AK fighter figures. Gani. Through this research, it is hoped that a spirit of love for the country will emerge among students, the younger generation, in order to create future generations who love their region and nation, as well as creating the next generation of the nation with character. This research uses historical methods using literature studies and interviews. Literature study is carried out by reviewing various relevant literature and reading materials and then analyzing and interpreting them so that they become written form. The results of this research are A.K. Gani is a figure during the physical revolution who deserves to be emulated, especially in efforts to instill character related to local history in the nation's next generation.